Coal petrology of the Yimin Formation (Albian) in the Hailar Basin, NE China: Paleoenvironments and wildfires during peat formation. (August 2021) - Wang, Shuai; Shao, Longyi; Li, Jiaxu; Li, Jianan; Jones, Timothy; Zhu, Mingyu; Zhou, Jiamin
Abstract: Coal seams preserve continuous and high-resolution records of paleoenvironments and wildfire events during peat accumulation. In order to elucidate wildfire characteristics and terrestrial climate changes during the time of peat accumulation, petrographic characteristics of coals in the Lower Cretaceous Yimin Formation (Albian) in the Jiuqiao Sag, Hailar Basin, NE China were studied. Coal petrology analysis shows that the studied coal seams are characterized by dominant huminite (average 80.0 vol.%, mmf-mineral matter free), secondary inertinite (average 19.9 vol.%, mmf), and a very low mineral content (average 0.8 vol.%). These results suggest that the coal developed under waterlogged conditions in raised, ombrotrophic mires. The occurrence of moderate inertinite values in the coals implies that wildfires were frequent during the Albian. Burning temperature, ranging from 273 to 379 °C inferred from inertinite reflectances, indicates that wildfires during the Albian were ground fires because of low plant heights. Vertical trends in inertinite and huminite compositional changes within the coal seams may reflect local-scale, cyclic fluctuations in wildfire occurrence during the development of the peat mires. The likely cause of these fluctuations was changes in temperature and rainfall. The presence of significant levels of inertinite in the coals and inferred high atmospheric oxygen levels suggest that the Albian was a highly fire-prone period in the Hailar Basin. The recurrent occurrences of palaeo-wildfires events in the studied succession in the Hailar Basin reinforce that fire was an important element affecting wetland biodiversity during the Albian, while diversification and spread of angiosperms was taking place globally. Increased surface runoff and erosion after the palaeo-wildfires in the Jiuqiao Sag during the Albian may have enhanced the flux and availability of nutrients and sediments washing into the fluvial, lacustrine, and marine systems, further contributing to the Albian dysoxic-anoxic events. Highlights: Vertical huminite and inertinite compositional changes within the coals in the Jiuqiao Sag may reflect local cyclic fluctuations in temperature and rainfall. The recurrent occurrences of palaeo-wildfire events in the studied succession in the Hailar Basin reinforce that fire was a significant element reaching wetland biodiversity during the Albian, while diversification and spread of angiosperms was taking place globally. The increasing of surface runoff and erosion after the palaeo-wildfires in the Jiuqiao Sag during the Albian may have influenced the flux and availability of nutrients, and the sedimentation as well, in the related fluvial, lacustrine and marine systems, more or less contributing to the Albian marine anoxic events.